Elvira Lacaci’s children’s literature: values of progress in a conservative context (Ogigia. Revista Electrónica de Estudios Hispánicos, 2022)
The children's literature of Elvira Lacaci (1918-1997), a writer from Ferrol, Spain, includes poetry and short stories. She developed it in the historical context of the Spanish post-war period, and it shows an oscillation between conservative approaches and the influx of advanced ideas related particularly to the incipient environmentalism, the opposition to racism and the denouncement of animal suffering. This study explores these concerns, adopting a methodology derived from literary criticism to analyse the texts, with emphasis on the poems. It also offers the worldview of a writer who was highly representative of her time - she was the first woman to win the Adonáis Poetry Prize - and whose books for children were widely distributed. In the same way, his article attempts to rescue the children's poetic facet due to its suitability for reading in the present and its application to the field of education.
Keywords: children’s literature; values; Elvira Lacaci